2012
DOI: 10.1007/s10900-012-9554-z
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Acceptability and Uptake of Human Papilloma Virus Vaccine Among Cameroonian School-Attending Female Adolescents

Abstract: The purpose of this study is to assess awareness, knowledge and beliefs about HPV, cervical cancer HPV vaccine and willingness to vaccinate among adolescent females aged 12-26 years at clinics and schools in the North West Region of Cameroon where the Cameroon Baptist Convention Health Services (CBCHS) conducted a sensitization and education campaign. A questionnaire survey was administered among female adolescents in schools and clinics. Descriptive statistics including frequencies, percentages and proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 39 publications
3
34
2
Order By: Relevance
“…Of these, 14/45 (31 %) experiences in nine countries formally measured acceptability in surveys, studies or post-introduction evaluations; the remainder reported acceptability without detailed methods. Studies in three countries measured vaccine acceptability as parents’ and/or girls’ willingness to be vaccinated and subsequent uptake of HPV vaccination [3133]. One study in one country specifically selected vaccinated and unvaccinated girls to survey [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 14/45 (31 %) experiences in nine countries formally measured acceptability in surveys, studies or post-introduction evaluations; the remainder reported acceptability without detailed methods. Studies in three countries measured vaccine acceptability as parents’ and/or girls’ willingness to be vaccinated and subsequent uptake of HPV vaccination [3133]. One study in one country specifically selected vaccinated and unvaccinated girls to survey [22].…”
Section: Resultsmentioning
confidence: 99%
“…Publications on experiences in Brazil, Cameroon, Kenya, Peru, South Africa, Tanzania, Uganda, and Vietnam reported parental acceptability [6, 22, 27, 3032, 3739]. Acceptability among girls was reported in Cameroon, Tanzania, Uganda, and Vietnam [22, 26, 33, 35, 36]: “Interestingly, girls who did not normally attend schools would often come to the school on vaccination day to receive their vaccines.” (KII, Country 25) …”
Section: Resultsmentioning
confidence: 99%
“…Physicians have been recognized as a strong influence for vaccine uptake in the USA (Rosenthal et al, 2011); however the differing health roles in low-income countries requires other healthcare workers (i.e. nurses) also be educated and approving of the vaccine (Ayissi et al, 2012). Studies piloting and evaluating actual uptake of the HPV vaccine within SSA have supported the prediction of high acceptance within these countries.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges can be addressed (at least in part) with communication and social marketing strategies, including: (a) raising awareness that cervical cancer only affects women; (b) marketing vaccine delivery as a package of cervical-cancer prevention tools, which also includes screening for women; and/or (c) integrating HPV vaccination into other health outreach or school-health programs so that girls are vaccinated as part of broader public-health interventions rather than singled out. Integration into school health efforts has been effectively achieved in other African countries [19, 29, 38], though cost and delivery challenges may impede the long-term sustainability of such efforts and there is a need for further delivery strategies to reach girls not in school, who may be in greatest need [39]. A combination of school-based and health facility-based delivery methods may therefore offer the greatest promise for effectively reaching girls with HPV vaccination in LMICs such as Kenya [40].…”
Section: Discussionmentioning
confidence: 99%